Antiperinuclear factor in juvenile rheumatoid arthritis. Issue 3 (March 1992) - Nesher, G; Moore, T L; Grisanti, M W; el-Najdawi, E; Osborn, T G
Abstract : The serological diagnosis of juvenile rheumatoid arthritis (JRA) is difficult, with only 7-10% of patients 19S IgM rheumatoid factor positive. About 60-70% of patients are positive for hidden 19S IgM rheumatoid factor, but this test requires serum separation and is not available in most laboratories. Antiperinuclear factor has been described in both seropositive and seronegative adult patients with rheumatoid arthritis, but has not been thoroughly evaluated in children with JRA. This study determined the diagnostic sensitivity and specificity of antiperinuclear factor in patients with JRA. Serum samples from 64 children with JRA, 24 with systemic lupus erythematosus (SLE), and 24 control subjects were tested for the presence of antiperinuclear factor. A total of 10 (83%) of seropositive, polyarticular onset and six (37%) of seronegative, polyarticular onset patients with JRA were positive for antiperinuclear factor. The occurrence of antiperinuclear factor in five (19%) with pauciarticular onset and one (10%) with systemic onset (JRA) as well as in four (17%) with SLE was not increased compared with the control subjects (1/24 (4%)). These data show an overall diagnostic sensitivity and specificity of 34 and 90% respectively in this group of patients. Although less sensitive than the hidden rheumatoid factor assay, the antiperinuclear factor assay is easier to perform and may contribute to the serological diagnosis of JRA.